The Effect of Chitinase-3-Like Protein 1 (YKL-40) Levels in the Plasma of Babylon Women with Breast Cancer - Shemran, Khawla A.; Najm, Zainab Mohsen; Abbass Ali, Zinah; Kadhim, ‎Hawraa Mudheher (Medical Science Journal for Advance Research, 2024)
Background: Breast cancer (BC) is a kind of cancer that starts in the breast. patients in addition to doctors are disturbed by survival prognosis. Besides, the prognostic factor has been the clinic pathological parameter linked to tumor consequences. Also, this cancer type possesses the biggest uprising rate of frequency as well as number two in rates of mortality in female’ cancers. migration of cancer cells starting the primary tumor and the invasion of cancer cells in the adjacent tissue are the primary steps in cancer metastasis. The present education aims to evaluate Chitinase-3-Like Protein 1 (YKL-40) levels in Babylon women with breast cancer and control groups. Material and methods: The case-control group was made up of 60 subjects, presumably healthy women, whereas the sick group was made up of 60 women with breast cancer. A study was conducted in Marjan Medical City, Imam Al-Sadiq Hospital, and AL-Hilla Teaching Hospital in Hilla City, between 2/11/2023 and April 29/4/2024. An ELISA was used to calculate the plasma concentrations that referred to Chitinase-3-Like Protein 1 (YKL-40). SPSS software was used to conduct the statistical analysis. Results: Despite a considerable increase in Chitinase-3-Like Protein 1 levels, with patients comparing it together with the control group (p < 0.05). Conclusion: women with breast cancer had considerably increased serum levels of Chitinase-3-Like Protein 1 levels. Based on the results of this investigation, this indicates the part of Chitinase-3-similar to Protein 1 as a prognostic marker within females with BC disease.